2015
DOI: 10.3923/ajcn.2015.33.44
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients Supplementation during Preconception Period Improves Fetal Survival and Cord Blood Insulin-Like Growth Factor 1

Abstract: The objective of this study was to evaluate the efficacy of multi-micronutrients (MMN) supplementation during preconception period on improving fetal survival and concentration of umbilical cord Insulin-like Growth Factor 1 (IGF-1). A randomized double blind community based trial had been conducted. Study subjects were randomly assigned into two groups (n = 210 in each group), namely multi-micronutrient group (MMN group) and placebo-iron folic acid group (Placebo-IFA group). The MMN group received capsule of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Unique studies included 37 RCTs, 3 cluster RCTs and 18 quasi-experimental studies (table 1). 18 19 30–93…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unique studies included 37 RCTs, 3 cluster RCTs and 18 quasi-experimental studies (table 1). 18 19 30–93…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight studies examined nutritional interventions. Of these, 10 studies examined multiple micronutrient supplementation 18 35 41 45 50 53 56 63 64 66 76 85 87 89. Five studies, including one study which also had a multiple micronutrient supplementation arm, examined iron and folic acid supplementation 18 39 46 47 56 58 65.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent systematic reviews have found the beneficial roles of multiple micronutrients (MMNs) over IFA when supplemented during pregnancy (8,9). There have been published clinical trials that have investigated the efficacy of different MMN supplements during preconception on birth outcomes, and the results have been variable (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The World Health Organization (WHO) in 2016 "did not recommend" MMN supplementation during pregnancy; however, in 2020, this was revised to "recommended in the context of rigorous research" (22).…”
Section: Introductionmentioning
confidence: 99%
“…Iron status and several micronutrients status also affected a pregnancy and its outcomes. Both animal studies and human observational studies evidenced that micronutrients deficiency in pre-pregnancy or during pregnancy was associated with a poor pregnancy or neonate (Ronnenberg, 2004;Bodnar, 2006;Catove, 2007;Beard, 2007;Sri Sumarmi, 2015). The low quality of the newborn baby was probably caused by not a single micronutrient deficiency, but by multiple micronutrients deficiency (Sunawang, 2009;Bhutta, 2009;Cetin, 2010;Kawai, 2011;Black, 2013).…”
Section: Introductionmentioning
confidence: 99%